ELEMENT CONTENTS OF SOIL AND LEAVES AND THEIR CORRELATION IN FIVE TREE SPECIES IN AN AREA OF THE RESERVA BIOLOGICA ALBERTO BRENES, COSTA RICA - Birkelbach, Jens (Universidad de Costa Rica, Sede de Occidente, 2012)
There are several reasons causing an increased research activity in the sector of tropical ecological research and conservation: the sorrow that one of the richest and most complex terrestrial ecasystems on earth is further logged and vanishing without ever been really understood; the fear of the global effect of this development on our earth: and the sorrow about the loss of immense genetic resources.